Influence of Mulch and Biofertilizer on Growth and Yield of Tomato - Singh, S. K.; Thakur, Ashok K.; Sharma, H. R.; Shukla, Arti; Singh, Upender (International Journal of Bio-resource and Stress Management, 2023)
The present study comprised of three genotypes (V1-Naveen 2000+, V2-Sun-7711 and V3-Solan Lalima), three mulches (M0-No mulch, M1-Pine needle mulch and M2-black polyethylene) and three biofertilizers (B0-recommended NPK, B1-100% NPK+Azotobacter (1 g plant-1)+PSB (1 g plant-1) and B2-75% NPK+Azotobacter (1 g plant-1)+PSB (1 g plant-1). Thus, there were 27 treatment combinations which were replicated thrice in split-split plot design. Among varieties, number of days to first flowering and first harvest and maximum yield was observed with the variety V2 (Sun-7711). Among the mulch materials and biofertilizers, M2 (Black polythene) and B1 (100% NPK+Azotobacter (1 g plant-1)+PSB (1 g plant-1) were recorded to be the best regarding number of days to first flowering and first harvest and fruit yield. The first order interactions viz., varieties×mulch, biofertilizers×mulch and varieties×biofertilizers significantly affected most of the characters under study. Maximum fruit yield was obtained with treatment combinations of V2M2 (Sun-7711 applied with black polyethylene mulch), B2M2 (75% NPK+Azotobacter (1 g plant- 1)+PSB (1 g plant-1) applied with black polyethylene mulch) and V2B2 (Sun-7711with 75% NPK+Azotobacter (1 g plant-1)+PSB (1 g plant-1). Further in three factor interaction, the highest fruit yield (1037.33 q ha-1) was obtained with the treatment combination of Sun-7711, 75% NPK+Azotobacter (1 g plant-1)+PSB (1 g plant-1) and black polyethylene mulch (V2B2M2).